Cost and cost-effectiveness of BPaL regimen used in drug-resistant TB treatment in the Philippines - D. Evans; K. Hirasen; D.J. Casalme; M.T. Gler; A. Gupta; S. Juneja (IJTLD Open)
BACKGROUND: In 2022, the WHO announced that the 6-month BPaL/M regimen should be used for drug-resistant TB (DR-TB). We estimate the patient and provider costs of BPaL compared to current standard-of-care treatment in the Philippines.METHODS: Patients on BPaL under operational research, or 9–11-month standard short oral regimen (SSOR) and 18–21-month standard long oral regimen (SLOR) under programmatic conditions were interviewed using the WHO cross-sectional TB patient cost tool. Provider costs were assessed through a bottom-up and top-down costing analysis.RESULTS: Total patient costs per treatment episode were lowest with BPaL (USD518.0) and increased with use of SSOR (USD825.8) and SLOR (USD1,023.0). Total provider costs per successful treatment were lowest with BPaL (USD1,994.5) and increased with SSOR (USD3,121.5) and SLOR (USD10,032.4). Compared to SSOR, BPaL treatment was cost-effective at even the lowest willingness to pay threshold. As expected, SLOR was the costliest and least effective regimen.CONCLUSIONS: Costs incurred by patients on BPaL were 37% (95% CI 22–56) less than SSOR and 50% (95% CI 32–68) less than SLOR, while providers could save 36% (95% CI 21–56) to 80% (95% CI 64–93) per successful treatment, respectively. The study shows that treatment of DR-TB with BPaL was cost-saving for patients and cost-effective for the health system.